2021
DOI: 10.1037/fsh0000642
|View full text |Cite
|
Sign up to set email alerts
|

Educating during the COVID-19 pandemic: The motherwork of Black women nursing professionals.

Abstract: Introduction:The purpose of this study was twofold: (a) explore how Black women perceive their roles as nursing professionals during the COVID-19 pandemic, and (b) how Black women in nursing mobilized themselves to respond to the disproportionate numbers of Black Americans impacted by COVID-19. Method: I conducted semistructured interviews with 6 Black women nursing professionals (5 nurse practitioners and 1 registered nurse). Data were analyzed in 3 cycles: eclectic coding, focused coding, and identifying sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…1 ). Of these, 320 articles were selected for full-text review to assess their relevance to our inclusion criteria, and 131 articles were included for the review ( Shahram et al., 2017 ; Hulko, 2009 ; Ngum Chi Watts et al., 2014 ; Kim and DeMarco, 2022 ; Thomas and Lightman, 2022 ; Edwards, 2021 ; Isaac, 2020 ; Sodré de Souza and Hiromi Tanaka, 2022 ; Kailemia et al., 2023 ; Duijs et al., 2023 ; Nepali et al., 2023 ; Haghiri-Vijeh, 2022 ; Lane, 2023 ; Holmgren et al., 2014 ; López et al., 2023 ; Cicero et al., 2023 ; Klusaritz et al., 2023 ; Aburizik et al., 2023 ; Acosta and Morris McEwen, 2023 ; Hill et al., 2023 ; Kemei et al., 2023 a; Kemei et al., 2023 b; Kemei et al., 2023 c; Luhanga et al., 2023 ; Keshet et al., 2015 ; Manca et al., 2022 ; Mehra et al., 2023 ; OjiNjideka Hemphill et al., 2023 ; Ojukwu et al., 2023 ; Salami et al., 2022 ; Nogueira et al., 2023 ; Small et al., 2022 ; Wiegand et al., 2023 ; O'Mahony et al., 2023 ; Pimienta et al., 2023 ; Giesbrecht et al., 2015 ; Crawford et al., 2023 ; Cuesta and Rämgård, 2016 ; McConnell et al., 2016 ; Höglund et al., 2016 ; Holmström et al., 2017 ; MacDonnell et al., 2017 ; Freeman et al., 2017 ; Guruge et al., 2010 ; Caiola et al., 2017 ; Coleman-Minahan, 2017 ; Van Dyke et al., 2017 ; Jörgensdotter Wegnelius and Petersson, 2018 ; Holtmann and Rickards, 2018 ; Pe...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Of these, 320 articles were selected for full-text review to assess their relevance to our inclusion criteria, and 131 articles were included for the review ( Shahram et al., 2017 ; Hulko, 2009 ; Ngum Chi Watts et al., 2014 ; Kim and DeMarco, 2022 ; Thomas and Lightman, 2022 ; Edwards, 2021 ; Isaac, 2020 ; Sodré de Souza and Hiromi Tanaka, 2022 ; Kailemia et al., 2023 ; Duijs et al., 2023 ; Nepali et al., 2023 ; Haghiri-Vijeh, 2022 ; Lane, 2023 ; Holmgren et al., 2014 ; López et al., 2023 ; Cicero et al., 2023 ; Klusaritz et al., 2023 ; Aburizik et al., 2023 ; Acosta and Morris McEwen, 2023 ; Hill et al., 2023 ; Kemei et al., 2023 a; Kemei et al., 2023 b; Kemei et al., 2023 c; Luhanga et al., 2023 ; Keshet et al., 2015 ; Manca et al., 2022 ; Mehra et al., 2023 ; OjiNjideka Hemphill et al., 2023 ; Ojukwu et al., 2023 ; Salami et al., 2022 ; Nogueira et al., 2023 ; Small et al., 2022 ; Wiegand et al., 2023 ; O'Mahony et al., 2023 ; Pimienta et al., 2023 ; Giesbrecht et al., 2015 ; Crawford et al., 2023 ; Cuesta and Rämgård, 2016 ; McConnell et al., 2016 ; Höglund et al., 2016 ; Holmström et al., 2017 ; MacDonnell et al., 2017 ; Freeman et al., 2017 ; Guruge et al., 2010 ; Caiola et al., 2017 ; Coleman-Minahan, 2017 ; Van Dyke et al., 2017 ; Jörgensdotter Wegnelius and Petersson, 2018 ; Holtmann and Rickards, 2018 ; Pe...…”
Section: Resultsmentioning
confidence: 99%
“…(2021) 18 USA NR Deficit-based Explore Black women's experiences of racism during pregnancy Race, pregnancy NR Duijs et al. (2023) 23 Netherlands 2019–2020 Deficit-based Explore potential threats to the health and well-being of self-employed care workers Gender, class, race, migration and age Critical theory Edwards (2021) 6 California, North Carolina, South Carolina; USA 2020 Both strength-based and deficit-based Explore the perception of Black women nurse's roles during the COVID-19 pandemic and their views on the impact of COVID-19 on Black Americans Race, gender NR Elliott et al. (2018) 11 Canada 2013 Deficit-based Explore the creation of a transitional care unit within an existing 20 bed rural Canadian hospital that introduced unregulated care providers to the care team and how this change affected the nursing team culture and leadership General social positions and relationships (non-specific) Critical social theory Ferlatte et al.…”
Section: Resultsmentioning
confidence: 99%
“…Although the research on these professionals during the pandemic is scant, studies have found that nurses engage in motherwork to better care for Black patients, 12 and mental health practitioners experience vicarious trauma and burnout, and practice advocacy for their patients. [13][14][15] Given the rise in attention and activities within the Black Lives Matter movement amid the global pandemic in 2020, elevating Black women healthcare professionals' experiences offer insight into how they navigated the pandemics, how health institutions responded to their employees, and possible modifications to ensure culturally competent efforts and strategies are implemented.…”
Section: Introductionmentioning
confidence: 99%